2020
DOI: 10.2478/sjph-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Telecardiology in Dealing with Patients with Cardiac Rhythm Disorders in Family Medicine – Systematic Review

Abstract: PurposeHeart rhythm disorders (HRD) are often present in patients visiting their family physician (FP). Dealing with their problems is not always simple, efficient and cost effective. The aim of this paper is to review the existing literature about the use and experience of telecardiology in patients experiencing HRD.MethodsWe conducted a review of literature in PubMed biographical databases (MeSH thesaurus), Web of Science and Cochrane, between 1995 and 2019. We included original articles in English that desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…There is extensive literature regarding telecardiology and teleultrasound diagnosis effectiveness. Vodicka et al in a systematic review regarding telecardiology in Slovenia concluded that telecardiology significantly reduces the number of unnecessary referrals to a cardiologist or hospitalization, and shortens the time needed to treat patients with life-threatening conditions [21]. Britton et al in a systematic review showed that teleultrasound provided satisfactory quality and value for clinical diagnosis and management [22].…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive literature regarding telecardiology and teleultrasound diagnosis effectiveness. Vodicka et al in a systematic review regarding telecardiology in Slovenia concluded that telecardiology significantly reduces the number of unnecessary referrals to a cardiologist or hospitalization, and shortens the time needed to treat patients with life-threatening conditions [21]. Britton et al in a systematic review showed that teleultrasound provided satisfactory quality and value for clinical diagnosis and management [22].…”
Section: Discussionmentioning
confidence: 99%
“…Telemonitoring is a subset of telemedicine and refers to the transmission of physiological data, such as BP and BG values, via automated electronic means or via web-based or telephone data. The data received allows physicians to interpret the data synchronously and make timely decisions about the patient's treatment (5)(6)(7). Currently, telemonitoring is often combined with teleconsultations, which can be synchronous via videoconferencing devices or asynchronous via email, internet, or mobile phones (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The data received allows physicians to interpret the data synchronously and make timely decisions about the patient's treatment (5)(6)(7). Currently, telemonitoring is often combined with teleconsultations, which can be synchronous via videoconferencing devices or asynchronous via email, internet, or mobile phones (5)(6)(7). The combination of frequent BP/BG measurements and timely feedback/consultation from the registered nurse or physician is the main reason why telemonitoring has the potential to significantly improve clinical outcomes (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on efficiently diagnosing such patients through telemedical approaches or remote consultations [ 16 , 17 ]. Remote consultations can be very useful in general practice because the patient and their GP need not to be at the same place at the same time [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This concept was developed in 1980s in order to provide healthcare to patients who live in remote areas [ 19 ] and has been shown to be very useful in times of lockdown—such as the COVID-19 pandemic [ 20 ]—when patients are not allowed to visit their GP due to restrictions [ 21 ] or are not comfortable doing so because of their fear of being infected with the virus [ 22 ]. Various low-cost sensors have been used to record the physiological parameters of patients, such as body temperature, heart rate, oxygenation of blood, and blood pressure [ 16 , 17 , 23 ]. Sensors are connected, by Wi-Fi or Bluetooth, to a smart phone or tablet and can be managed using different applications [ 24 ].…”
Section: Introductionmentioning
confidence: 99%